Leadership and Organizational Culture in Driving Employee Performance - Damarsari Ratnasahara Elisabeth; Mochamad Fathurrohman; Joko Suyono; Awan Panjinata (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: To examine the influence of leadership and organizational culture on employee performance with motivation as a mediating variable. Design/methodology/approach: This study employs a quantitative approach using SEM-PLS analysis based on data collected from 83 employees through questionnaires. Findings: Leadership and organizational culture have a positive and significant influence on employee performance, both directly and indirectly through motivation as a mediating variable. Research limitations/implications: This study is limited to a single company and a relatively small sample, suggesting future research should expand the scope and variables. Practical implications: Organizations should strengthen leadership quality and organizational culture to enhance employee motivation and ultimately improve performance. Originality/value: This study provides empirical evidence on the mediating role of motivation in linking leadership and organizational culture to employee performance in the maritime service sector. Paper type: Research paper (quantitative study)